Analysis of Strengthening Youth Organizations in Lolowua Village, Hiliserangkai District Nias Regency, Indonesia - Mendrofa, Yarman; Halawa, Odaligoziduhu; Ndraha, Ayler B.; Lahagu, Palindungan (Golden Ratio of Data in Summary, 2024)
The purpose of this study is to analyze the strengthening of youth organization activities in Lolowua Village, Hiliserangkai District, Nias Regency, to analyze how obstacles to strengthening youth organizations in lolowua village and to analyze how efforts are made in strengthening youth organizations in lolowua village. This type of research is qualitative. Data analysis techniques use data reduction, data presentation and conclusion drawn. The result of this study is that the Capacity Strengthening of the Youth Organization in Lolowua village has not run optimally, this is because there are still several obstacles to indicators that are not yet effective, The main factors that become obstacles are lack of budget that limits the implementation of programs and activities, lack of adequate human resources, ineffective communication, and limited facilities, Lack of training and mentoring for member capacity, low participation from members and the community. The efforts made in strengthening the Youth Organization in Lolowua Village pay special attention to the youth organization, monitoring, evaluation of management and programs, involving the youth organization in the planning to strengthen human resources, improve communication, provide better facilities, and increase participation and training for all members of the Youth Organization.